An institutional vision for public debt in Brazil - Leite, Marcel Guedes; Arvate, Paulo Roberto (Brazilian Journal of Political Economy, 2002)
The purpose of this article is found a theoretical apology to the debt public allocation on agents’ finance wealth given the successive defaults enforced by public sector to debt public demanding. JEL Classification: H6.